Electrochemical Oxidative Selenation of 4H‐Pyrido‐[1, 2‐a]‐pyrimidin‐4‐ones with Diorganyldiselenides. Issue 1 (3rd January 2023) - Chen, Jinyang; Xiao, Yao; You, Xianhui; Li, Shiqi; Fu, Yuwei; Ouyang, Yuejun
Abstract: An environmentally friendly protocol for the synthesis of C3 ‐selenylated 4H‐pyrido[1, 2‐ a ]pyrimidin‐4‐ones was developed via the electrochemical oxidation, iodide‐catalyzed selenation of 4H‐pyrido[1, 2‐ a ]pyrimidin‐4‐ones with diaryl (alkyl) diselenides under oxidant‐ and external electrolyte‐free conditions. Only by using 10 mol % of KI as catalyst and electrolyte, the selenation can proceed efficiently, and give corresponding products in good to excellent yields, avoiding the use of excess oxidant or iodinated reagents. Abstract : An environmentally friendly protocol for the synthesis of C3 ‐selenylated 4H‐pyrido[1, 2‐a]pyrimidin‐4‐ones was developed via the electrochemical oxidation, iodide‐catalyzed selenation of 4H‐pyrido[1, 2‐a]pyrimidin‐4‐ones with diaryl(alkyl)diselenides under oxidant‐ and external electrolyte‐free conditions. The KI plays a dual role as both a catalyst and electrolyte during the selenation.